A Combined Experimental and Computational Study of Linear Ruthenium(II) Coordination Oligomers with End‐Capping Organic Redox Sites: Insight into the Light Absorption and Charge Delocalization. Issue 37 (6th August 2013) - Yao, Chang‐Jiang; Zheng, Ren‐Hui; Nie, Hai‐Jing; Cui, Bin‐Bin; Shi, Qiang; Yao, Jiannian; Zhong, Yu‐Wu
Abstract Two series of linear ruthenium coordination oligomers, [(Ntpy)Run(tppz)n−1(tpy)]2n+ (mono‐Ntpy series, n=1–3) and [(Ntpy)2Run(tppz)n−1]2n+ (bis‐Ntpy series, n=1–3) have been prepared, where Ntpy is the capping ligand 4′‐di‐p‐anisylamino‐2, 2′:6′, 2′′‐terpyridine, tppz is tetra‐2‐pyridylpyrazine, and tpy is 2, 2′:6′, 2′′‐terpyridine. The electrochemical measurements evidence oxidation events from both the amine segments and the metal centers and reduction waves from tppz and the capping ligands. Both series complexes display much enhanced light absorption with respect to model complexes without terminal amine units. Density functional theory (DFT) calculations have been performed on both series and time‐dependent DFT (TD‐DFT) calculations have been performed on the bis‐Ntpy‐series compounds (n=1–4) to characterize their electronic structures and excited states and predict the electronic properties of long‐chain polymers. Upon one‐electron oxidation, the mono‐Ntpy‐series monoruthenium and diruthenium complexes display N+‐localized transitions and metal‐to‐nitrogen charge‐transfer (MNCT) transitions in the near‐infrared (NIR) region. DFT and TD‐DFT computations on the one‐electron‐oxidized forms of the mono‐Ntpy‐series compounds (n=1–4) provide insight into the nature of the MNCT transitions and the degree of charge delocalization.